Reprograming Carcinoma Associated Fibroblasts by microRNAs - Xu, Y.; Zhou, X.; Mei, M.; Ren, Y. (Current Molecular Medicine, 2017)
Carcinoma-associated fibroblasts (CAFs) are activated fibroblasts during development of several cancer types, and therefore emerge as an attractive therapeutic target for cancer therapy. Drugs such as PT-100 and sibrotuzumab that block the functions of CAFs have already been in clinical trials. However, these drugs exhibit limited efficacy in patients, partially due to the fact that currently used biomarkers for determining efficacy are not CAF-specific. Furthermore, depletion of CAFs may promote carcinogenesis and accelerate cancer progression by inducing immunosuppression and hypoxia, leading to reduced survival. Accumulating evidence demonstrates that restoring the expression of key microRNA induces the functional conversion of CAFs into normal fibroblasts by targeting different signaling pathways and metabolic mechanisms. Therefore, reprograming CAFs into normal fibroblasts by altering specific expression of microRNAs, rather than targeted ablation, may be an effective, novel strategy for cancer treatment. This review focuses on specific microRNAs involved in the transformation of CAFs as well as their multiple roles during tumorigenesis and chemo-resistance.
Keywords: metabolic pathway